Question
upstudy study bank question image url

\( \arg \frac { ( 2 + 2 i ) ( 1 + i \sqrt { 3 } ) } { 3 i ( \sqrt { 12 } - 2 i ) } \)

Ask by Bryant Ward. in Sweden
Nov 06,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

The argument of the complex expression is \( \tan^{-1}\left(\frac{-2 - 3\sqrt{3}}{-5 - 4\sqrt{3}}\right) \).

Solution

To find the argument of the complex expression \[ \arg \frac{(2 + 2i)(1 + i\sqrt{3})}{3i(\sqrt{12} - 2i)}, \] we can use the property that the argument of a quotient is the difference of the arguments: \[ \arg \frac{z_1}{z_2} = \arg z_1 - \arg z_2. \] Let \( z_1 = (2 + 2i)(1 + i\sqrt{3}) \) and \( z_2 = 3i(\sqrt{12} - 2i) \). ### Step 1: Calculate \( \arg z_1 \) First, we calculate \( z_1 = (2 + 2i)(1 + i\sqrt{3}) \). Calculating \( z_1 \): \[ z_1 = 2(1 + i\sqrt{3}) + 2i(1 + i\sqrt{3}) = 2 + 2i\sqrt{3} + 2i - 2\sqrt{3} = (2 - 2\sqrt{3}) + (2\sqrt{3} + 2)i. \] Now, we find the argument of \( z_1 \): \[ \arg z_1 = \tan^{-1}\left(\frac{\text{Im}(z_1)}{\text{Re}(z_1)}\right) = \tan^{-1}\left(\frac{2\sqrt{3} + 2}{2 - 2\sqrt{3}}\right). \] Simplifying the fraction: \[ \frac{2\sqrt{3} + 2}{2 - 2\sqrt{3}} = \frac{2(\sqrt{3} + 1)}{2(1 - \sqrt{3})} = \frac{\sqrt{3} + 1}{1 - \sqrt{3}}. \] To simplify further, we can multiply the numerator and denominator by the conjugate of the denominator: \[ \frac{(\sqrt{3} + 1)(1 + \sqrt{3})}{(1 - \sqrt{3})(1 + \sqrt{3})} = \frac{(\sqrt{3} + 1 + 3 + \sqrt{3})}{1 - 3} = \frac{4 + 2\sqrt{3}}{-2} = -2 - \sqrt{3}. \] Thus, \[ \arg z_1 = \tan^{-1}(-2 - \sqrt{3}). \] ### Step 2: Calculate \( \arg z_2 \) Next, we calculate \( z_2 = 3i(\sqrt{12} - 2i) \). Calculating \( z_2 \): \[ z_2 = 3i\sqrt{12} - 3i(2i) = 3i\sqrt{12} + 6 = 6 + 3i\sqrt{12}. \] Now, we find the argument of \( z_2 \): \[ \arg z_2 = \tan^{-1}\left(\frac{\text{Im}(z_2)}{\text{Re}(z_2)}\right) = \tan^{-1}\left(\frac{3\sqrt{12}}{6}\right) = \tan^{-1}\left(\frac{\sqrt{12}}{2}\right) = \tan^{-1}(2\sqrt{3}). \] ### Step 3: Combine the arguments Now we can find the argument of the original expression: \[ \arg \frac{z_1}{z_2} = \arg z_1 - \arg z_2 = \tan^{-1}(-2 - \sqrt{3}) - \tan^{-1}(2\sqrt{3}). \] Using the tangent subtraction formula: \[ \tan(a - b) = \frac{\tan a - \tan b}{1 + \tan a \tan b}, \] where \( a = \tan^{-1}(-2 - \sqrt{3}) \) and \( b = \tan^{-1}(2\sqrt{3}) \). Let \( x = -2 - \sqrt{3} \) and \( y = 2\sqrt{3} \): \[ \tan(a - b) = \frac{x - y}{1 + xy} = \frac{(-2 - \sqrt{3}) - (2\sqrt{3})}{1 + (-2 - \sqrt{3})(2\sqrt{3})}. \] Calculating the numerator: \[ -2 - \sqrt{3} - 2\sqrt{3} = -2 - 3\sqrt{3}. \] Calculating the denominator: \[ 1 + (-2)(2\sqrt{3}) - \sqrt{3}(2\sqrt{3}) = 1 - 4\sqrt{3} - 6 = -5 - 4\sqrt{3}. \] Thus, \[ \tan(a - b) = \frac{-2 - 3\sqrt{3}}{-5 - 4\sqrt{3}}. \] The argument can be expressed as: \[ \arg \frac{(2 + 2i)(1 + i\sqrt{3})}{3i(\sqrt{12} - 2i)} = \tan^{-1}\left(\frac{-2 - 3\sqrt{3}}{-5 - 4\sqrt{3}}\right). \] This is the final expression for the argument. Thus, the final answer is: \[ \arg \frac{(2 + 2i)(1 + i\sqrt{3})}{3i(\sqrt{12} - 2i)} = \tan^{-1}\left(\frac{-2 - 3\sqrt{3}}{-5 - 4\sqrt{3}}\right). \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the argument of the expression \( \arg \frac { ( 2 + 2 i ) ( 1 + i \sqrt { 3 } ) } { 3 i ( \sqrt { 12 } - 2 i ) } \), we can start by simplifying the argument step-by-step. 1. **Calculate the numerator:** \((2 + 2i)(1 + i\sqrt{3}) = 2 \cdot 1 + 2 \cdot i \sqrt{3} + 2i \cdot 1 + 2i \cdot i\sqrt{3}\) \(= 2 + 2i\sqrt{3} + 2i - 2\sqrt{3}\) Combine real and imaginary parts: Real part: \(2 - 2\sqrt{3}\) Imaginary part: \(2 + 2\sqrt{3}i\) So, the numerator simplifies to \( (2 - 2\sqrt{3}) + (2 + 2\sqrt{3})i \). 2. **Calculate the denominator:** \(3i(\sqrt{12} - 2i) = 3i(\sqrt{12}) - 3i(2i) = 3i\sqrt{12} + 6\) Simplifying further, since \( \sqrt{12} = 2\sqrt{3} \): \(= 3 \cdot 2\sqrt{3}i + 6\) Combine: \(6 + 6\sqrt{3}i\). 3. **Putting it all together:** Now we need \( \arg\left( \frac{(2 - 2\sqrt{3}) + (2 + 2\sqrt{3})i}{(6 + 6\sqrt{3}i)} \right) \). Using the property that \( \arg(z_1/z_2) = \arg(z_1) - \arg(z_2) \): - For the numerator \( (2 - 2\sqrt{3}) + (2 + 2\sqrt{3})i \): \((2 - 2\sqrt{3}) = r_1\) and \((2 + 2\sqrt{3}) = \theta_1\): \(r_1 = \sqrt{(2-2\sqrt{3})^2 + (2 + 2\sqrt{3})^2} \) The argument (using \(\tan^{-1}\)) can also be applied. - For the denominator \( 6 + 6\sqrt{3}i \): Again, calculate the argument by summing the angle measures. 4. **Final step:** Combine both to find the complete argument: \(\text{Final Argument} = \arg\text{(numerator)} - \arg\text{(denominator)}\). Thus, the result is a calculation based on the angles obtained from each piece before direct evaluation, resulting subsequently in the final answer.

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy